El rol de las redes sociales en la comprensión oral de segundas lenguas con soporte móvil - Bárcena, Elena; Read, Timothy (Miscelánea: A Journal of English and American Studies, 2019)
Oral comprehension is an important competence for a second language learner but one that requires significant practice and guidance. Considerable literature exists on the factors that appear to play a role in the development of oral comprehension, which can be classified as perceptual, cognitive or metacognitive, and in the teaching and learning strategies that support this process. A MALL (Mobile Assisted Language Learning) app, called the Audio News Trainer (ANT), was developed by the authors to support students in the development of oral comprehension, by presenting them with audio news recordings together with related learning activities. There are two versions of the app, one for individual use and another one that is connected to Facebook to reinforce psychopedagogical aspects relevant in the development of oral comprehension. Two research questions are explored in this article, regarding the use of this social network to motivate students and help them become more self-regulated; and they are addressed by means of questionnaires and experimental data gathered using ANT. The results obtained from such analyses show that the guided interaction between second language students in the social network Facebook made a significant impact in terms of the students’ motivation and self-regulation measurable in their development of oral comprehension.
Keywords: oral comprehension; mobile-assisted language learning; social networks; motivation; self-regulation